Referral pattern and co-management of keratoconus patients in primary eye care: A survey of three European countries. Issue 3 (June 2022) - Rahmani, M.; Ortiz-Toquero, S.; Martin, R.
Abstract: Purpose: To explore current primary care practices in keratoconus management in Portugal and compare with previous reported results in two European countries (the UK and Spain), with a special focus on interdisciplinary collaboration and referral practice patterns. Methods: An online survey adapted to European professional practice was distributed (via newsletters) by the Portuguese Optometrist Association to explore keratoconus patient management and referral practice patterns among Portuguese practitioners. Results: Responses of 119 optometrists were compared with previous reported of 464 eye-care practitioners (126 in the UK and 338 in Spain). Most respondents (79% in Portugal, 71% in the UK and 76% in Spain; p = 0.31) had < 5 new keratoconus patients each year. No accepted referral criterion was found (p < 0.01) because small number of the respondents (14%) in Portugal referred out at initial diagnosis (50% in the UK and Spain); 32% referred out when progression was detected (17% in the UK and 30% in Spain); and a minority (10% in Portugal, 9% in the UK, and 6% in Spain) referred out when visual acuity was affected. A majority of respondents (83%) in Portugal reported no co-management with ophthalmologists (60% in the UK and 73% in Spain; p < 0.01). Conclusion: The results of this study suggest that it is necessary to encourage interdisciplinary collaboration between practitioners to improve referral of patients with suspected keratoconus to an ophthalmology specialist to change the course of this disease, to reduce keratoconus progression and visual acuity impairment and to minimize the impact of this disease on patients' quality of life.